Intrainfusion Drug Monitoring and Algorithm-Based Dose Adjustments for Children With ALL Receiving High-Dose Methotrexate Are Feasible and Safe in Costa Rica, a Low- and Middle-Income Country - Karol Acevedo; Gabriela Soto; Mary C. Shapiro; Jennifer H. Foster; Kathia Valverde; Eric S. Schafer; Judith Margolin (JCO Global Oncology)
PURPOSEInfusions of high-dose methotrexate at 5 g/m2 over 24 (HDMTX) as a single infusion for pediatric patients with high-risk precursor B-cell ALL are known to lead to superior outcomes. The Hospital Nacional de Niños Dr Carlos Sáenz Herrera, part of the public system Caja Costarricense de Seguro Social in Costa Rica (HNN), has been historically unable to provide this therapy secondary to the required intensive monitoring and cost-prohibitive toxicity support.METHODSWe report our experience providing HDMTX at HNN, to our knowledge, for the first time using an algorithm-based individualized HDMTX protocol designed to prevent toxic levels of methotrexate. The protocol checks intrainfusion methotrexate levels at hours 2 and 6 or 8, with adjustments in the infusion downward if levels predict a high/toxic end infusion concentration.RESULTSFifty-two patients (who received 196 total evaluable infusions between 2017 and 2019) were included. Rate adjustments were required during 51 infusions (24.6%). Significant methotrexate-related toxicities were rare and included acute kidney injury (≥grade 3, 0.5%, n = 1), neurotoxicity (≥grade 3, 1%, n = 2), mucositis (≥grade 3, 4.8%, n = 10), and neutropenia (≥grade 3, 24.6%, n = 51). No ≥grade 4 toxicities occurred.CONCLUSIONA real-time, algorithm-based individualized HDMTX infusion is a practical and safe way to administer HDMTX in a low- and middle-income country.